Numerical study of gas-fines flow characteristics in a packed bed with the presence of internal blocks. (20th January 2011) - Gunjal, V.V.; Lollchund, M.R.; Gupta, G.S.
It is well-known that pulverised coal injection in an iron-making blast furnace improves the furnace productivity and stability. However, with increase in the injection rate of the pulverised coal, some amount of coal remains unburnt. In the form of powder, the unburnt coal flows along with the gas and under certain conditions accumulates in the lower part of the blast furnace. This results in deterioration of the permeability and decreases the production rate. This work focuses on the mathematical modelling of a packed bed in a view to study the aerodynamics of gas-fines flow which is essential to understand the interaction between the phases and improve the furnace performance. In the model, blocks are inserted to represent typical cohesive zones in a blast furnace. The gas decreasing velocity condition is employed as it represents the flow behaviour in a blast furnace more accurately and it has not been considered in published work. The model provides a clear picture of the gas-fines flow characteristics in the packed bed.